Ghrelin and pre-proghrelin immunoreactive cells in gastric neuroendocrine tumors associated with atrophic body gastritis - Moreira,Letícia Figueiredo (2010)
INTRODUCTION: Ghrelin is a 28 amino acid peptide secreted mainly by endocrine cells present in the gastric mucosa and acknowledged as an endogenous releaser of growth hormone. The immunohistochemical expression of ghrelin has been described in neuroendocrine tumors, and it is believed that may exert modulating action related to the growth of these tumors. OBJECTIVE: To study the presence of ghrelin and preproghrelin immunoreactive cells in gastric neuroendocrine tumors associated with atrophic body gastritis. METHODS: Endoscopic biopsies from 15 patients with neuroendocrine tumor of the gastric mucosa associated with atrophic body gastritis were performed for immunohistochemistry, and specific chromogranin, ghrelin and preproghrelin antibodies were applied. The immunohistochemical expression was assessed in tumor cells and endocrine micronodular hyperplasia present in mucosa adjacent to the tumor, and it was classified in relation to the number of stained cells. RESULTS: Chromogranin was positive in 14 out of 15 tumors. Ghrelin and preproghrelin immunoreactive cells were detected in 11 (73%) and 13 (87%) tumors, respectively. There was a significant correlation between the immunohistochemical results of both antigen expressions (kappa = 81%). Ghrelin and preproghrelin expression was detected in hyperplastic nodules present in the mucosa adjacent to the tumor in seven and eight cases, respectively. There was no correlation between these results and those observed in neoplastic cells. CONCLUSION: Ghrelin and preproghrelin immunoreactive cells may be found in variable number in Type I neuroendocrine gastric tumors and in hyperplastic nodules associated with these tumors. However, it remains unclear what role these peptides play on the development of these tumors.